Increasing Tourist Intention To Visit Of Coastal And Marine Tourism Visits Through Digital Marketing - Dadan Sumantri; Taufiq Rahmat (Jurnal Manajerial, 2023)
Background – The Covid-19 pandemic has made the world economy to experience a sharp decline, especially in the tourism sector. One of the tourism sectors affected is coastal and marine tourism. To increase the number of tourists again, many researchers state that digital marketing has a significant role. Aim – This study aims to examine the used model of digital marketing used by coastal and marine tourism actors so that they can be optimized to increase tourism attractiveness. Design / methodology / approach – The method used in this research is to use six steps, namely strategy determination, planning, training, data collection, review, and reporting. Research data collection will be carried out using a questionnaire survey method. Findings – According to the findings, digital marketing through websites and Instagram factors can affect tourism attractiveness but cannot affect intention to visit. However, the intention to visit in this study can be influenced by tourism attractiveness. Research implication – Tourism providers must consider what factors can increase tourism attractiveness, such as by using digital marketing tools. The local government can also increase the facility in the tourism destination. Limitations – Future studies can consider other factors in digital marketing, as this study only considers websites and Instagram as the too. Other factors, such as email marketing, search engine optimization, content marketing, and the use of mobile applications should be explored by future researcher.